1992
DOI: 10.1007/bf02403898
|View full text |Cite
|
Sign up to set email alerts
|

Wear behaviour of aluminium matrix composite materials

Abstract: Wear behaviour of aluminium matrix composites is characterized by the dry spindle wear test under various conditions (volume fractions of reinforcements, sliding distances and speeds). Wear resistance of composites is improved due to the presence of reinforcements, but no noticeable improvements are observed in the wear resistance with more than 20% addition of reinforcements. To anatyse wear mechanisms, wear surfaces are examined by scanning electron microscopy (SEM). The major wear mechanisms of discontinuou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(16 citation statements)
references
References 12 publications
2
11
0
Order By: Relevance
“…The results obtained are similar with those obtained by Lee et al. 23 who have reported that the wear mechanisms are strongly dependent upon the sliding speeds. At low speed, the wear rate is lower since the damage caused to the tribolayer formed between the mating surfaces is less, while under high speeds, there is a breakdown of the tribolayer leading to excessive wear.…”
Section: Discussionsupporting
confidence: 91%
“…The results obtained are similar with those obtained by Lee et al. 23 who have reported that the wear mechanisms are strongly dependent upon the sliding speeds. At low speed, the wear rate is lower since the damage caused to the tribolayer formed between the mating surfaces is less, while under high speeds, there is a breakdown of the tribolayer leading to excessive wear.…”
Section: Discussionsupporting
confidence: 91%
“…Aluminum-based MMCs overcome the above limitation and find utility in advanced engineering applications. 12,[27][28][29][30] A wide range of aluminum alloys are used for the production of aluminumbased MMC. Pure aluminum melts at 660 C, which makes easy processing of AMCs through various fabrication methods.…”
Section: Tribological Aspectsmentioning
confidence: 99%
“…Tool rotational speed is the most important process parameter in FSP which has greater influence in uniform distribution of reinforcement particles, grain refinement and heat input during the process. Many researchers have given their valuable contributions in preparing surface composites by the use of FSP technique with various reinforcement particles like SiC, Al 2 O 3 , Al 3 Ti on the surface of Aluminum alloy 6061-T6 [7][8][9][10]. MMCs prepared by addition of single or mixture of two or more different types of particles with certain volume fractions into the parent alloy.…”
Section: Introductionmentioning
confidence: 99%